La décadence à la fin du XIXe siècle espagnol: une esthétique de la provocation - Escudero, Xavier (Nordlit, 2012)
Talking about Decadence in fin-de-siècle Hispanic literature involves delving into the great movement of modernism, and notably one of its expressions, literary bohemianism. In what way(s) do these concepts both make use of and take part in an aesthetic of transgression, or a provocative pose? What does Spanish decadentism really mean, and what are its expressions? In order to answer these questions, we shall first look at the concept of decadentism as applied to the sociocultural phenomenon of Spanish literary bohemianism, which gathers writers and artists defined by constant failure, loose morals and the "cursed" poses they adopt. Then we shall highlight the literary expressions of decadence through the writings of Manuel Machado, Rubén Darío and Ramón María del Valle-Inclán, three prominent authors of the fin-de-siècle letters. Finally we shall take a closer look at the decadent motifs of marginality and lust in the little-known field of modernist bohemian poetry.